Genomic and proteomic evidence supporting the division of the plant pathogen Ralstonia solanacearum into three species. (December 2016) - Prior, Philippe; Ailloud, Florent; Dalsing, Beth; Remenant, Benoit; Sanchez, Borja; Allen, Caitilyn
Abstract Background The increased availability of genome sequences has advanced the development of genomic distance methods to describe bacterial diversity. Results of these fast-evolving methods are highly correlated with those of the historically standard DNA-DNA hybridization technique. However, these genomic-based methods can be done more rapidly and less expensively and are less prone to technical and human error. They are thus a technically accessible replacement for species delineation. Here, we use several genomic comparison methods, supported by our own proteomic analyses and metabolic characterization as well as previously published DNA-DNA hybridization analyses, to differentiate members of theRalstonia solanacearum species complex into three species. This pathogen group consists of diverse and widespread strains that cause bacterial wilt disease on many different plants. Results We used three different methods to compare the complete genomes of 29 strains from theR. solanacearum species complex. In parallel we profiled the proteomes of 73 strains using Matrix-Assisted Laser Desorption/Ionization-Time of Flight Mass Spectrometry (MALDI-TOF-MS). Proteomic profiles together with genomic sequence comparisons consistently and comprehensively described the diversity of theR. solanacearum species complex. In addition, genome-driven functional phenotypic assays excitingly supported an old hypothesis (Hayward et al. (J Appl Bacteriol 69:269–80, 1990)), that closely related members of theR. solanacearum could be identified through a simple assay of anaerobic nitrate metabolism. This assay allowed us to clearly and easily differentiate phylotype II and IV strains from phylotype I and III strains. Further, genomic dissection of the pathway distinguished between proposed subspecies within the current phylotype IV. The assay revealed large scale differences in energy production within theR. solanacearum species complex, indicating coarse evolutionary distance and further supporting a repartitioning of this group into separate species. Conclusions Together, the results of these studies support the proposed division of theR. solanacearum species complex into three species, consistent with recent literature, and demonstrate the utility of proteomic and genomic approaches to delineate bacterial species.